Focal Adhesion Kinase Regulates Expression of Thioredoxin-interacting Protein (TXNIP) in Cancer Cells - Ho, Baotran; Huang, Grace; Golubovskaya, Vita M. (Anti-Cancer Agents in Medicinal Chemistry, 2014)
Focal Adhesion Kinase (FAK) plays an important role in cancer cell survival. Previous microarray gene profiling study detected inverse regulation between expression of thioredoxin-interacting protein (TXNIP) and FAK, where down-regulation of FAK by siRNA in MCF-7 cells caused up-regulation of TXNIP mRNA level, and in contrast up-regulation of doxycyclin- induced FAK caused repression of TXNIP. In the present report, we show that overexpression of FAK in MCF-7 cells repressed TXNIP promoter activity. Treatment of MCF-7 cells with 1alpha, 25-dihydroxyvitamin D3 (1,25D) down-regulated endogenous FAK and up-regulated TXNIP protein level, and treatment with 5-FU decreased FAK protein expression and up-regulated TXNIP protein expression in 293 cells. Moreover, silencing of FAK with siRNA increased TXNIP protein expression, while overexpression of FAK inhibited TXNIP protein expression in 293 cells. In addition, treatment of DBTRG glioblastoma cells with FAK inhibitor Y15 increased TXNIP mRNA, decreased cancer cell viability and increased apoptosis. These results for the first time demonstrate FAK-regulated TXNIP expression which is important for apoptotic, survival and oxidative stress signaling pathways in cancer cells.
Keywords: breast cancer